Repositioning coal power to accelerate net-zero transition of China’s power system - Kangxin An; Xinzhu Zheng; Jianxiang Shen; Canyang Xie; Can Wang; Wenjia Cai; Chujie Bu (Nature Communications)
Abstract Countries are urged to advance the energy transition in a just, orderly, and equitable manner, yet the appropriate pathway remains unclear. Using a provincial-level, hourly-dispatched power system model of China that incorporates intertemporal decisions on early retirement and carbon capture retrofitting, our study reveals that for coal-rich but gas-poor economies, repositioning coal power from a baseload resource to a flexibility provider can accelerate net-zero transition of the power system in three aspects. First, when achieving the same emissions reduction target, it mitigates stranded assets by decreasing the average lifespan loss of coal power by 7.9-9.6 years and enhancing the long-term competitiveness of retrofitted coal power. Second, it enables the integration of an additional 194-245 gigawatts of variable renewables by 2030 under the same carbon emissions reduction trajectory. Third, it reduces China’s power system transition costs by approximately 176 billion U.S. Dollars, particularly in the face of costly gas power and energy storage technologies. These robust findings underscore the need for appropriate policies to incentivize the flexible dispatch, orderly retirement, and carbon capture retrofitting of coal power, thereby accelerating the decarbonization of China’s power system.